2018
DOI: 10.1097/qai.0000000000001616
|View full text |Cite
|
Sign up to set email alerts
|

Retention in HIV Care During Pregnancy and the Postpartum Period in the Option B+ Era: Systematic Review and Meta-Analysis of Studies in Africa

Abstract: Retention rates in prevention of mother-to-child transmission under option B+ were below those of the general adult population, necessitating interventions targeting the complex circumstances of women initiating care under option B+. Improved and standardized procedures to track and report retention are needed to accurately represent care engagement and capture undocumented transfers within the health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
207
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(237 citation statements)
references
References 67 publications
23
207
7
Order By: Relevance
“…Our findings add to the limited literature on retention of postpartum women in Africa beyond 12 months on ART . Overall retention at 12 and 24 months after ART initiation (71% and 65% respectively) were broadly comparable to reports from other parts of sub‐Saharan Africa.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our findings add to the limited literature on retention of postpartum women in Africa beyond 12 months on ART . Overall retention at 12 and 24 months after ART initiation (71% and 65% respectively) were broadly comparable to reports from other parts of sub‐Saharan Africa.…”
Section: Discussionsupporting
confidence: 80%
“…Younger age was a shared risk factor for not linking to care, more frequent mobility, non‐retention and raised VL. This adds to the substantial evidence indicating that younger HIV‐positive women are often at increased risk for poor treatment outcomes . Although associations were small, younger age, timing of presentation for ANC and relationship status could flag women requiring additional support to link to care postpartum.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In sub‐group analyses, retention in care did not significantly worsen after Treat All implementation among those with more advanced HIV (as indicated by CD4 count) or among men and younger patients, who have traditionally been at risk of worse outcomes. Among patients referred to HIV care from maternal/prenatal clinics, there was no significant change in six‐month retention after Treat All implementation, and overall retention at six months was higher than in studies of pregnant women initiating HIV care under Option B+ programmes in other settings . Additional research is needed to determine whether the observed results reflect a population‐wide benefit of Treat All, even to at‐risk groups, or may be a function of Rwanda's already high‐performing HIV programme.…”
Section: Discussionmentioning
confidence: 87%